Too good to be true? How time-inconsistent renewable energy policies can deter investments - Nils May; Olga Chiappinelli (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The transition towards low-carbon economies requires massive investments into renewable energies, which are commonly supported through regulatory frameworks. Yet, governments can have incentives - and the ability - to deviate from previously-announced support once those investments have been made, which can deter investments. We analyze a renewable energy regulation game, apply a model of time-inconsistency to renewable energy policy and derive under what conditions governments have incentives to deviate from their commitments. We analyze the effects of various support policies and deployment targets and explain why Spain conducted retrospective changes in the period 2010-2013 whereas Germany stuck to its commitments.
Keywords: Q42; Q55; O38; C73; 330; Time-Inconsistency; Regulation; Targets; Renewable Energy Policy; Investments